2017
DOI: 10.3390/ijerph14040345
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Evidence for Bacterial Determinants Influencing Obesity Development

Abstract: Obesity is a major global public health problem requiring multifaceted interventional approaches including dietary interventions with probiotic bacteria. High-throughput genome sequencing of microbial communities in the mammalian gastrointestinal system continues to present diverse protein function information to understand the bacterial determinants that influence obesity development. The goal of the research reported in this article was to identify biological processes in probiotic bacteria that could influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…Intake of a whey protein isolate has also been reported to specifically increase the abundance of Lactobacillaceae/Lactobacillus (Figure 1) and decrease the abundance of Clostridiaceae/Clostridium (McAllan et al, 2015), and in comparison to casein, whey protein intake was reported to increase the levels of Lactobacilli and Bifidobacteria in a rat model of colitis (Sprong, Schonewille, & van der Meer, 2010). Several species of Lactobacilli have been reported to reduce adiposity in mice and be associated with weight-loss in humans (Park et al, 2013;Yoo et al, 2013;Isokpehi, Simmons, Johnson, & Payton, 2017) suggesting that protein-associated changes in the gut microbiota might be causally linked with improved metabolic function. However, it remains to be established whether such changes in the composition of the gut microbiota are causally related to the anti-obesogenic actions of specific proteins such as milk and plant proteins.…”
Section: Effect Of Proteins On Microbiotamentioning
confidence: 97%
“…Intake of a whey protein isolate has also been reported to specifically increase the abundance of Lactobacillaceae/Lactobacillus (Figure 1) and decrease the abundance of Clostridiaceae/Clostridium (McAllan et al, 2015), and in comparison to casein, whey protein intake was reported to increase the levels of Lactobacilli and Bifidobacteria in a rat model of colitis (Sprong, Schonewille, & van der Meer, 2010). Several species of Lactobacilli have been reported to reduce adiposity in mice and be associated with weight-loss in humans (Park et al, 2013;Yoo et al, 2013;Isokpehi, Simmons, Johnson, & Payton, 2017) suggesting that protein-associated changes in the gut microbiota might be causally linked with improved metabolic function. However, it remains to be established whether such changes in the composition of the gut microbiota are causally related to the anti-obesogenic actions of specific proteins such as milk and plant proteins.…”
Section: Effect Of Proteins On Microbiotamentioning
confidence: 97%
“…Increased proportions of Lactobacillus have been observed in high fat diet fed mice (Clarke et al, 2013 ). However, certain species of Lactobacillus , such as Lactobacillus plantarum (Isokpehi et al, 2017 ) were recently associated with weight-loss in humans. Further, supplementation with Lactobacillus curvatus HY7601 and L. plantarum KY1032 in diet-induced obese mice was associated with gut microbial changes and reduction in obesity (Park et al, 2013 ).…”
Section: Protein Sources Gut Microbiota and Obesitymentioning
confidence: 99%
“…In addition, Bifidobacteria-fermented whey and cheese protein have expressed decreased populations of Bacteroides fragilis and Clostridium perfingens , increased acetate production, and greater Lactobacillus and Bifidobacterium diversity [ 170 , 171 , 172 ]. Moreover, certain Lactobacillus and Bifidobacteria species have been associated with increased muscle strength, weight loss, and reduced obesogenic environments in humans and rodents [ 173 , 174 , 175 , 176 ]. This may be attributed to whey protein’s abundance in Lactobacillus and Bifidobacteria , as reported in rodent studies [ 177 , 178 , 179 ].…”
Section: Sarcopenic Obesity: a Case For Protein And Gut Microbiotamentioning
confidence: 99%